Theoretical nuclear physics in Italy : proceedings of the 11th Conference on Problems in Theoretical Nuclear Physics : Cortona, Italy, 11-14 October 2006 - Conference on Problems in Theoretical Nuclear Physics 2006 : Cortona, Italy); Covello, A. (Aldo) (Hackensack, N.J. : World Scientific, 2007)
This volume gives a comprehensive overview of the latest research activity undertaken in the field of theoretical nuclear physics in Italy. Several topics of current interest are included: from nuclear matter and nuclear structure to nuclear astrophysics and quark?gluon plasma.
Remembering Professor Adelchi Fabrocini -- Learning many-body physics with Adelchi -- Few-nucleon systems -- Three-nucleon continuum states within the hyperspherical adiabatic method -- Bakamjian-Thomas mass operator for the few-nucleon system: an effective theory approach -- Electromagnetic reactions on few-nucleon systems -- Isospin mixing in the 4He bound state and the nucleon strange form factor -- Nuclear matter and nuclear dynamics -- Quantum Monte Carlo calculations of symmetric nuclear matter -- Nuclear structure -- An equations of motion method for the exact solution of the nuclear eigenvalue problem in a multiphonon space -- New results in the CBF theory for medium-heavy nuclei -- Unbound exotic nuclei studied by projectile fragmentation -- Fully microscopic calculations for closed-shell nuclei with realistic nucleon-nucleon potentials -- Spatial dependence of pairing field induced by the exchange of collective vibrations -- Nuclear astrophysics -- Hartree Fock Bogoliubov calculation of the pinning energy of vortices on nuclei in the inner crust of neutron stars -- Gamma-Ray-Bursts and quark phases -- Hybrid protoneutron stars within a static approach -- Processes of burning and convection in compact objects -- Nuclear physics with electroweak probes -- 4He photodisintegration with a realistic nuclear force -- Testing superscaling predictions in electroweak excitations of nuclei -- Strange quark effects in electron and neutrino-nucleus quasi-elastic scattering -- Hadron structure and hadronic matter -- Instantons and the non-perturbative quark dynamics in the chiral regime -- Electromagnetic form factors of the nucleon in spacelike and timelike regions -- Nucleon form factors in point-form spectator-model constructions -- Chiral-odd generalized parton distributions, transversity and double transverse-spin asymmetry in Drell-Yan dilepton production -- Unquenching the quark model -- Tetraquark states and spectrum -- Quark-Gluon Plasma and relativistic heavy ion collisions -- Phases of QCD: lattice thermodynamics, quasiparticles and Polyakov loop -- I Laboratori Nazionali del Sud -- Nuclear structure at the Legnaro National Laboratories: from high intensity stable to radioactive nuclear beams -- Experimental nuclear physics with INFN.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Nuclear physics -- Congresses; Nuclear physics -- Research -- Italy -- Congresses; Physique nucléaire -- Congrès.; Physique nucléaire -- Recherche -- Italie -- Congrès.; SCIENCE -- Physics -- Nuclear; SCIENCE -- Physics -- Atomic & Molecular; Nuclear physics; Nuclear physics -- Research; Italy; Conference papers and proceedings